Parameter Design of Current-sharing Reactor Utilized by Energy Feedback Converter for Urban Rail Transit Vehicle - WENG Xingfang; WANG Xiong; LIN Wenbiao; XIE Xiangjian; SONG Qianru (Kongzhi Yu Xinxi Jishu)
Aiming to the circulation between parallel modules of energy feedback converter, it analyzed the causes of unbalanced-flow between parallel converter modules and the working principles of current-sharing reactors, and then proposed a new method of coil winding for current-sharing reactor to restrain the circulation. It described the calculation and selection of electrical parameters of current-sharing reactor in detail, simulated the working condition of current-sharing reactor and thus realized the rationalized design. Experimental results of a developing project for DC 750V energy feedback device prove the feasibility of the current-sharing design.